Cytotoxicity testing of alkaloid compounds isolated from sponge Petrosia sp: its potency for development of anticancer agent - Astuti, Puji; Alam, Gemini; Hartati, Mae Sri; Sari, Dinar; Wahyuono, Subagus (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2005)
Cancer is still a major problem and common cause of death around the world. Various therapeutic agents have been developed to fight against cancer, but none of these agents give satisfactory results and without debilitating side effects. A number of researches have been conducted to search anticancer compounds with renewed vigour.Sponges, marine invertebrates, are known as rich sources of compounds which pronounced pharmacological activities. The aims of this study are to determine cytotoxic effect of two toxic compounds isolated from chloroform fraction of Petrosia sp sponges collected from Bunaken on myeloma cells.The two toxic compounds were isolated based on bioassay guidedisolation on brine shrimp larvae. Isolation was conducted using column chromatography followed by preparative TLC. Cytotoxic effect of the two compounds was conducted in 96 well plate using RPMI 1640 as medium. The number of viable cells was determined using MTT assay and LC50 (Î¼g/mL) of the compounds was analysed using probit analysis.The results showed that the two compounds were alkaloid and toxic to larva A. salina with LC50 of 7.23 (compound 1) and 5.69 Î¼g/mL (compound 2). These compounds were also toxic to myeloma cells with LC50 values of 16.95 Î¼g/mL (compound 1) and 18.8 Î¼g/mL (compound 2). The longer the incubation time, the compounds were more toxic as showed by the lower LC50 values .Key words: cytotoxic, Petrosia sp, Artemia salina Leach, myeloma